The prevalence, immunogenicity, and evanescence of alloantibodies to MUT and Mur antigens of GP.Mur red blood cells in a Southeast Asian patient cohort - Nadarajan, Veera Sekaran (Wiley, 2018)
BACKGROUND: Antibodies to Mia , MUT, and Mur are among the most frequently identified alloantibodies in Southeast Asia. Understanding the characteristics of these antibodies in terms of induction and evanescence would aid in optimizing methods for their detection. STUDY DESIGN AND METHODS: Antibody testing results between the years 2013 and 2015 with relevant patient demographic data and red blood cell (RBC) transfusion history were retrieved. Cumulative alloimmunization incidence and evanescence to MUT and Mur were estimated by Kaplan-Meier analysis in relation to the number of RBC units transfused and time. RESULTS: Of 70,543 selected patients, 6186 nonalloimmunized subjects with available antibody testing results posttransfusion were identified. Cumulative alloimmunization incidence for MUT increased from 0.12% (95% confidence interval [CI], 0.03-0.21) to 0.63% (95% CI, 0.25-1.01), while for Mur it increased from 0.04% (95% CI, 0-0.09) to 0.42% (95% CI, 0.05-0.79) when a patient was transfused 2 RBC units as compared to 12. Both antibodies had high evanescence rates and at 1 year, anti-MUT and -Mur will be detected in only 45% (95% CI, 35%-57%) and 27% (95% CI, 17%-43%), respectively, of previously positive patients. MUT and Mur immunogenicity was estimated to be 1.7 and 1.2 times higher than E when their rate of evanescence was taken into account. CONCLUSION: Antibodies to MUT and Mur develop following multiple RBC exposures. Immunogenicity of MUT/Mur and evanescence rates of the corresponding antibodies is higher compared to anti-E. Appropriate selection of antibody screening cells is needed in view of the high prevalence, immunogenicity, and evanescence of the antibodies.